High Frequency of Salivirus in Pediatric Patients with Acute Gastroenteritis - Saber Basiri1; Bahman Khalesi2; Seyed Dawood Mousavi-Nasab3; Zahra Ivani4; Mostafa Ghaderi1 (Journal of Medical Microbiology and Infectious Diseases, 2021)
Introduction: Salivirus (SalV), a possible causative agent of gastroenteritis, belongs to the genus Salivirus in Picornaviridae Family. The fecal-oral path seems to be the entry route for SalV in susceptible peoples such as children that consume polluted water. We investigated the SalV occurrence in children's stool with acute gastroenteritis using a reverse transcription-quantitative polymerase chain reaction assay (RT-qPCR). Methods: From Sep. 2018 to May 2019, 160 stool samples were collected from children with acute gastroenteritis admitted to Imam Ali General Hospital, Alborz University of Medical Sciences, Iran. After viral RNA extraction, the 5'UTR region of the SalV genome was amplified by reverse transcriptionquantitative polymerase chain reaction (RT-qPCR), and the viral load was defined. Results: Of the 160 stool samples, 41 (25.6%) were positive for SalV RNA. The highest SalV detection rate was in Feb. (28.2%), and the highest viral load (6.2×107 copies/g) belonged to a 1-month-old patient. Conclusion: Salivirus occurs among Iranian children with acute gastroenteritis. Our results suggest that Salivirus might contribute to acute gastroenteritis.